Penentuan Kondisi Kualitas Perairan Muara Sungai Somber, Balikpapan, Kalimantan Timur dengan Metode Indeks Pencemaran (Pollution Index) - Marita Wulandari; Muhammad Ma’arij Harfadli; Rahmania Rahmania (LPPM ITK, 2020)
Balikpapan bay has an important and strategic role, such as a buffer for sustainability of the estuary function as the Balikpapan seaport. In Balikpapan esuary watershed there are large and small rivers, including Somber River. Settlements and industries around the river banks have caused a decrease of river water quality, especially activities that place pollutant loads (waste) on the river bodies. This research is focused on physical and chemical parameters, including Total Dissolved Solid (TDS), temperature, pH, and DO (Dissolved Oxygen).Water quality research was conducted by dividing the river into 7 measurment points. The distribution of measurement points was based on water quality considerations that represent upstream, middle, and downstream water quality, as well as considering easy access. Water samples at each mesurment point ware collected at three different depths (vertically). Concentrations of several parameters that have been obtained were then analyzed using the Pollution Index method (Pollution Index) which is used to determine relative pollutant levels to the allowed water quality parameters. The testing procedure by pollution index refers to procedure poured in the Decree of the State Minister for the Environment No. 115 in 2003 concerning of Determining Guidelines of Water Quality Status. Based on the field measurments, an average value for temperatures obtained ranging from 30.0 - 32.1 ° C, TDS values ​​4270 mg / L - 10000 mg / L, DO ranges between 1.8 mg / L - 3.1 mg / L, and pH values ​​between 6.6 - 7.1. From the calculation and data analisys of physical and chemical parameters, the research can be concluded that the location of measurement point 1 shows water quality status being lightly polluted, while point 2,3,4,5,6, and 7 shows water quality status being moderately polluted. Keywords: Water quality, estuary, Somber river, pollution index